Risk Mitigation in Tofu Production at PT. Tahu Jeletot Taisi, Depok, West Java - Isnaini Setia Hanif; Eny Dwiningsih; Rizki Adi Puspita Sari; Mudatsir Najamuddin; Mukhlis (Cita konsultindo, 2025)
This research aims to (1) Identify risk events and risk causes, (2) Know the level of risk, (3) Map risks, and (4) Formulate risk mitigation that can be applied in the production process of stuffed tofu at PT Tahu Jeletot Taisi. The data used are primary data and secondary data collected through observation, interviews, questionnaires, and literature studies. The analytical tools used are fishbone diagrams, House Of Risk (HOR), and pareto diagrams. Based on the research that has been done, 25 risk events and 28 risk causes are obtained in the entire series of tofu production processes at PT Tahu Jeletot Taisi. The results of measuring the risk of the highest ARP value in making tofu, namely the quality of soybeans is not good (A1), in frying tofu, namely turning the tofu too hastily (A16), and in making stuffed tofu, namely employees are less careful when splitting and filling the tofu (A26). The mapping results obtained 14 priority risk causes. 8 priority risk causes in tofu making, 3 priority risk causes in tofu frying, and 3 priority risk causes in stuffed tofu making. Then there are 20 risk mitigations recommended to PT Tahu Jeletot Taisi, namely 10 risk mitigations in making tofu, 4 risk mitigations in frying tofu, and 6 risk mitigations in making stuffed tofu.